POLYSEMY OF PHRASEOLOGICAL UNITS IN RUSSIAN AND UZBEK:A COMPARATIVE ASPECT - S.R.Baratova (Western European Studies, 2025)
The article is devoted to the little-studied phenomenon of phraseological polysemy in the Russian and Uzbek languages. Comparative analysis of multivalued correlates revealed a complex picture of the relationship between the meanings of FE in the Russian and Uzbek languages, confirming the hypothesis that two multivalued phraseological units of different languages in rare cases correspond to all their meanings.
Keywords: phraseological unit; phraseological polysemy; contrastive analysis